Toward ultra-long cycling stability and high lithium storage performances: Silica anodes with catalytic effects of low-cost metals particles. (December 2021) - Cheng, Yong; Chen, Bingbing; Zhu, Mengyao; Chang, Limin; Zhang, Dongyu; Wang, Chunli; Wang, Shaohua; Wang, Limin
Highlights: SiO2 − M-C ( M  = Fe, Ni, Cu) composites have been prepared via a simple one-step high energy mechanical milling process. Transition metals (Fe, Ni, Cu) have catalytic effect in breaking Si-O and Li-O bonds during discharge/charge process. SiO2 -Fe-C reveals the highest initial coulombic efficiency and discharge capacity. Abstract: SiO2 has attracted considerable attention for the application of next-generation lithium-ion batteries (LIBs) because of its evident merits, such as large capacity, high natural abundance and low price. Nevertheless, the huge volume inflation and inferior electronic conductivity lead to material degradation and hamper its extensive use. To resolve these challenges, a series of SiO2 -M-C ( M  = Fe, Ni, Cu, C = acetylene black) composites are prepared via a straightforward high energy mechanical milling (HEMM) method. Herein, the M nanoparticles can boost the electronic conductivity and ameliorate electrochemical activity of SiO2 through the catalytic effect of M in breaking Si-O and Li-O bonds, while C can offer a highly conducting assistance to effectively deter agglomeration and pulverization of SiO2 nanoparticles. Superiorly, SiO2 -Fe-C reveals exceptional performances with a high initial Coulombic efficiency (CE) of 70.4% at 0.2 A g −1 and long cycle stability under different high current densities (335.6 mAh g −1 at 2 A g −1, 2000 cycles; 212 mAh g −1 at 5 A g −1, 5000 cycles, respectively), which surpasses the reported SiO2 -based materials. Considering the convenient preparation and outstanding properties, SiO2 -Fe-C can be of visible significance for practical application in next-generation LIBs. Graphic abstract: SiO2 − M-C ( M  = Fe, Ni, Cu) composites have been prepared via a simple one-step high energy mechanical milling process. Herein, the M nanoparticles not only can boost the electronic conductivity, but also can ameliorate electrochemical activity of SiO2 through the catalytic effect of M in breaking Si-O and Li-O bonds. SiO2 -Fe-C reveals the best electrochemical performances in terms of initial Coulombic efficiency and discharge capacity. Image, graphical abstract